A kinematics analysis of the Tsuhakara 3/1 in Yang Wei's vaulting horse - Li, J. (Journal of Beijing Sport University, 2006)
The Tsuhakara 3/1 is the most difficult act of vaulting horse at present, with the difficulty worth 7 points.There are only a few athletes who can accomplish this act. Being the key athlete of Chinese Gymnastics team, Yang Wei could master this act after several years of arduous efforts, and achieve a great success with it.With the video of three dimensions of this act of the first-hand materials of Yang Wei, we may get the acquisition of kinematics parameter of this act, and precede in technical analysis and diagnosis of it, by the data analytics. This thesis aims at unveiling the biomechanical regularity and kinematical pattern of the Tsuhakara 3/1 and providing technical analysis.